A mobile architecture for integration of smartphones with lbs for flora and fauna inventories (2013)
Smartphones currently have a large number of sensors and more processing capacity, allowing greater integration of a mobile architecture supported by an external Location Based System. The following paper will contextualize the architecture in a nature inventory with a strong mobile component in the data collection on site. It will integrate additional technologies like GPS, QR Codes and map deployment through the LBS.